Literature Review of Environment-Based Science Learning as an Effort to Foster Environmental Awareness in Students - Zalzabilla Sapphira; Benny Joy; Teguh Husodo (Green Publisher Indonesia, 2026)
Environmental problems remain among the most critical global issues. Various forms of environmental damage, such as pollution, ecosystem degradation, and the exploitation of natural resources, demonstrate the need for systematic efforts to foster an attitude of environmental care from an early age. Education plays a strategic role in shaping students' awareness of and attitudes toward the environment, particularly through the field of science, which is closely related to natural phenomena and the surrounding environment. Environment-based science learning is a relevant approach because it integrates scientific concepts with real environmental problems that are close to students’ daily lives. This study aims to comprehensively examine research findings related to environment-based science learning as an effort to foster students’ environmental care attitudes. The research method used is a literature review, conducted by analyzing reliable and relevant national and international journals published within the last 5–10 years that align with the topic. The results of this literature study indicate that environment-based science learning, implemented through various methods such as contextual learning, project-based learning, and environmental observation activities, can increase students’ attitudes of environmental care at various educational levels and across different subjects. This improvement is reflected in aspects of environmental awareness, responsibility, and pro-environmental behavior. These findings indicate that environment-based science learning is an effective approach and can be applied sustainably in science education to support the development of students’ environmental care character.